Piezoelectric enhanced photocatalytic properties of PVDF–ZnO/Cu nanofibers prepared by electrospinning technique - Atipong Bootchanont; Porramain Porjai; Russameeruk Noonuruk; Chakkaphan Wattanawikkam; Sorapong Pavasupree; Wantana Klysubun; Tirapat Wechprasit; Aphisit Maniwong; Wisanu Pecharapa (Polymer-Plastics Technology and Materials, 2022)
Piezoelectric-assisted photocatalysis technology is one of the efficient ways to achieve enhancement in photocatalytic performance by facilitating the separation of photoinduced electron and holes via internal field initiated via piezoelectricity. Herein, bi-piezoelectric integrated effect was generated by the combination of piezoelectric semiconductor photocatalyst ZnO/Cu and piezoelectric polymer polyvinylidene fluoride (PVDF). Firstly, ZnO/Cu nanoparticles were prepared by facile co-precipitation method. Then, nanoparticles (at 10–30 wt%) were loaded in PVDF for fabricating nanofibers by electrospinning technique. All PVDF–ZnO/Cu nanofibers were characterized by XRD, FE-SEM, FTIR, XAS, and UV–Vis DRS. The structural study indicates that the β- and α-phase PVDF is observed in all the prepared nanofibers. XANES technique confirms the oxidation state of 2+ for Zn and Cu ions in both nanoparticles and nanofibers. Furthermore, under the synergy action of ultrasonic and visible light irradiation, PVDF–ZnO/Cu nanofibers exhibit superior piezo-photocatalytic degradation of rhodamine B dye when compared with single light or mechanical excitation. Effects of ZnO/Cu concentration on optical, piezoelectric, and photocatalytic properties are discussed.
Keywords: Advanced Sensor and Energy Harvesting Materials; Electrospun Nanofibers in Biomedical Applications; Tactile and Sensory Interactions